The Effect of Soy Milk Consumption on Anxiety Levels in Menopause Women - Anastasia Ch. Inggrid Lumape; Raden Maria Veronika Widiatrilupi (Calory Journal Medical Laboratory Journal, 2025)
Menopause is a natural biological transition marked by declining estrogen levels and often accompanied by physical and psychological symptoms, including anxiety. More than half of women report significant anxiety during this stage, highlighting the need for safe, accessible interventions. Soy milk, rich in isoflavones functioning as phytoestrogens, offers potential as a non-pharmacological alternative. This study aimed to evaluate the effect of soy milk consumption on anxiety levels in menopausal women. Using a pre-test and post-test experimental design, 30 menopausal women aged 45–60 years were selected through purposive sampling. The intervention consisted of daily consumption of 200 ml soy milk for four weeks. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HAM-A) before and after intervention, with data analyzed using a paired t-test (p<0.05). Results showed a significant reduction in anxiety scores from 26.40±7.85 to 18.10±6.30 (mean difference 8.30, p=0.000). Prior to intervention, 66.7% of respondents experienced moderate to severe anxiety, while post-intervention 76.7% were categorized as none to mild. These findings suggest that soy milk effectively reduces anxiety in menopausal women through phytoestrogenic stabilization of hormonal fluctuations. Soy milk can be recommended as a safe, affordable complementary strategy, with further research needed to confirm long-term effects and optimal dosage.